2004
DOI: 10.1902/jop.2004.75.6.811
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and/or Calcium Plus Vitamin D Increase Mandibular Bone Mass

Abstract: The data of this study indicate that E/HRT and/or calcium and vitamin D may result in increases of mandibular bone mass in postmenopausal women. Because of the long-term risks associated with E/HRT, caution should be exercised in prescribing E/HRT for prevention of chronic menopausal conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 28 publications
0
27
0
5
Order By: Relevance
“…Although the beneficial effects of calcium and vitamin D supplementation on bone health have been well recognized, 27–29 their potential role in periodontal disease has not been fully determined. A number of studies 30–37 suggested that vitamin D and/or calcium intake results in reduced alveolar bone loss, gingival inflammation, and/or attachment loss. Most relevant are data on subjects (∼12,000) enrolled in the Third National Health and Nutrition Examination Survey (NHANES III), suggesting that lower dietary intake of calcium increased attachment loss in a dose‐dependent fashion 38 .…”
mentioning
confidence: 99%
“…Although the beneficial effects of calcium and vitamin D supplementation on bone health have been well recognized, 27–29 their potential role in periodontal disease has not been fully determined. A number of studies 30–37 suggested that vitamin D and/or calcium intake results in reduced alveolar bone loss, gingival inflammation, and/or attachment loss. Most relevant are data on subjects (∼12,000) enrolled in the Third National Health and Nutrition Examination Survey (NHANES III), suggesting that lower dietary intake of calcium increased attachment loss in a dose‐dependent fashion 38 .…”
mentioning
confidence: 99%
“…30) Although the effect of a calcium supplement on reducing bone loss was less than that of an estrogen treatment, 31) clinical studies have indicated that it was more effective than 1-hydroxyvitamin D 3 in preventing loss of BMD among elderly women over a four-year period. 32) Current research has revealed that hormone replacement therapy (HRT), accompanied by a calcium supplement 33) and monofluorophosphates or 1-hydroxyvitamin D 3 , can help increase BMD among postmenopausal women. 34) A supplement of calcium or of calcium and vitamin D is generally prescribed to osteoporotic patients undergoing treatment with alendronate, 35) clodronate, 36) ipriflavone, [37][38][39] calcitriol 40) and disodium palmidronate.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos mostraram que a DOM está fortemente correlacionada com o número de dentes remanescentes em mulheres na pós-menopausa e sugerem que a perda óssea sistêmica contribui para a perda dos dentes [16][17][18][19] . Porém, um estudo seccional não encontrou diferença significativa quando utilizados os parâmetros clínicos periodontais em 292 mulheres osteopênicas 20 no qual foram encontrados média de dentes presentes de 17,2±7 e PIC no valor de 2,8±0,9 mm.…”
Section: Densitometria óSsea Mineralunclassified
“…No entanto, analisando os grupos de mulheres estrógeno suficientes e deficientes, os parâmetros periodontais não mostraram tal associação, como apresentado em estudos semelhantes 13,16,21 . Estes estudos concluíram que a osteopenia na pós-menopausa constitui fator de risco para a doença periodontal.…”
Section: Densitometria óSsea Mineralunclassified